How does internet finance influence the interest rate? Evidence from Chinese financial markets - Luo Changqing; Mengzhen Li; Pin Peng; Siyuan Fan (Dutch Journal of Finance and Management, 2018)
It is gradually accepted that the Internet finance has increased the accessibility of financial market, and caused an important impact on the financial market. Considering the quick development of the Internet finance in China, we propose theoretical hypotheses to explain the influencing path of Internet finance on market interest rate. Then by using the data from May 2013 to November 2016, we apply UCINET diagram and vector autoregression model and variance decomposition methods to verify the theoretical hypotheses. The empirical results show the Internet finance lead to the change of market interest rate mainly through reference point effect of P2P interest rate. Although the Internet finance affects the social monetization and exchange rate, this impact cannot be passed to interest rate through the medium variables of social monetization and exchange rate.
Keywords: 650; Internet finance; interest rate; Chinese financial markets; network relation diagram